The use of curaua fibers as reinforcements in composites - Souza, S. F.; Ferreira, M.; Sain, M.; Ferreira, M. Z. [UNESP]; Pupo, H. F. [UNESP]; Cherian, B. M. [UNESP]; Leão, A. L. [UNESP] (Elsevier, 2014)
Nowadays, there is growing worldwide interest in the use of natural renewable materials to replace synthetic polymers or improve the properties of current materials. Natural fibers seem to offer a great opportunity in this respect, and among them curaua (. Ananas erectifolius L. B. Smith) fiber has unique properties, such as high strength, low density, a fine structure and high cellulose content. Due to its mechanical properties and recyclability, it is of great interest for developing composite materials. In addition, because of its high cellulose content, curaua fiber is one of the most potentially important sources of raw material for producing nanocellulose for use in the manufacture of nanocomposites.
Keywords: Composites; Curaua fiber; Mechanical properties; Nanofibers; Polymers; Reinforcement